Depression score and body mass index mediate the association between dietary vitamin C intake and female infertility: a study based on NHANES 2013–2018 - Zheng, Lingxin; Ren, Qingling; Tan, Yong (Frontiers in Nutrition, 2025)
BackgroundThe supplement of antioxidants to improve fertility has received widespread attention. The efficacy of the dietary antioxidant vitamin C (VC) on female infertility has not been fully elucidated. This study investigates the relationship between VC intake and infertility in terms of depression score and body mass index (BMI).MethodsOur cross-sectional study included 2,381 adult American females aged from 18 to 44 from the National Health and Nutrition Examination Survey (NHANES, 2013–2018) database. Multiple logistic regressions, smoothed curve fitting, mediation and sensitivity analysis were conducted to describe the relationship between VC intake and infertility.ResultsCompared to the low VC intake group (Q1), the probability of female infertility in the highest group (Q4) decreased by 39.4% (adjusted OR = 0.606; 95% CI: 0.419, 0.878, P = 0.008). A threshold non-linear association between VC and infertility was more significant in women aged from 18 to 34 (P = 0.033). Moreover, the relationship between VC and infertility was mediated by 5.28% depression (P = 0.034) and 7.83% BMI (P = 0.010), respectively.ConclusionsThe protective effect of VC on female fertility was most significant in the group with the highest VC intake. The association between VC intake and the likelihood of female infertility was non-linear and smallest infertility index occurred when VC intake reached 132.7 mg in women aged 18–34. Depression score and BMI seemed to mediate the relationship. However, further research was needed to confirm the interaction effects of VC, depression and BMI on female infertility from basic and clinical perspectives.